A global assessment of the oesophageal adenocarcinoma epidemic. Issue 10 (23rd August 2012) - Edgren, Gustaf; Adami, Hans-Olov; Weiderpass, Elisabete; Nyrén, Olof
Abstract : Objective: About 20 years ago, the scientific community was first alerted to an enigmatic increase of oesophageal adenocarcinomas in the UK and USA. Subsequently, a virtual epidemic—still unexplained—was confirmed in several western countries. Detailed descriptive data might provide clues to its causes. Design: We collected data on incident cases of oesophageal adenocarcinoma from population-based cancer registries in Australia, Europe, North America and Asia. We calculated age-standardised incidence rates and fitted log-linear Poisson models to assess annual rate of increase and to disentangle age-period-cohort effects, linear spine models to estimate rate of increase since 1985, and Joinpoint models to identify possible inflection points. Results: With considerable between-registry variation in magnitude and timing, we found a consistent dramatic increase in incidence with an observed or estimated start between 1960 and 1990. The average annual increase ranged from 3.5% in Scotland to 8.1% in Hawaii with similar proportional increase among men and women in most registries and a maintained three to sixfold higher incidence among men. Generally, calendar period was a more important determinant of incidence trends than birth cohort. Where possible to conduct, Joinpoint analyses indicated that the onset of the epidemic varied considerably even between neighbouring countries. Conclusions: Given the preponderant period effect and the abrupt onset observed or inferred in most populations, the epidemic appears to be caused by some exposure that was first introduced around 1950. At least 30 years' variation in estimated time of onset opens prospects for hypothesis-generating ecological analyses.